2008
DOI: 10.1175/2007waf2006074.1
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Surface Analyses over the Western United States to RAWS Observations

Abstract: Federal, state, and other wildland resource management agencies contribute to the collection of weather observations from over 1000 Remote Automated Weather Stations (RAWS) in the western United States. The impact of RAWS observations on surface objective analyses during the 2003/04 winter season was assessed using the Advanced Regional Prediction System (ARPS) Data Assimilation System (ADAS). A set of control analyses was created each day at 0000 and 1200 UTC using the Rapid Update Cycle (RUC) analyses as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Prior work has demonstrated that the near-surface boundary layer in the CONUS remains undersampled (Myrick and Horel 2008;Horel and Dong 2010). Figure 1 illustrates the need for additional observing capabilities, particularly in mountainous and coastal areas, in terms of an integrated data influence analysis (IDI; Uboldi et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior work has demonstrated that the near-surface boundary layer in the CONUS remains undersampled (Myrick and Horel 2008;Horel and Dong 2010). Figure 1 illustrates the need for additional observing capabilities, particularly in mountainous and coastal areas, in terms of an integrated data influence analysis (IDI; Uboldi et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…1 follows assumptions for those covariances (e.g., equal error variance for observations and background) discussed later and results in an IDI value of 0.5 near an isolated observation (i.e., the observation and background value receive equal weight there). Observation impacts have often been evaluated through cross-validation experiments, in which a control analysis using all observations is compared to an analysis in which observations of interest are excluded from the assimilation (Seaman and Hutchinson 1985;Zapotocny et al 2000;Myrick and Horel 2008;Benjamin et al 2010;Tyndall et al 2010;Horel and Dong 2010). 1 with many stations and enhanced data coverage (few observations) have IDI values much larger (smaller) than 0.5.…”
Section: Introductionmentioning
confidence: 99%
“…Figures 3 and 6 provide a gross indication of some of the largest data voids. Myrick and Horel's (2008) results for winter temperature over the western United States only, the removal of RAWS on average has a larger detrimental impact on analyses than removal of NWS stations (Table 6). Hence, the -value‖ of RAWS as examined here from the standpoint of analysis impact is higher than the value of NWS stations.…”
Section: Discussionmentioning
confidence: 96%
“…The land management agencies through their support of the RAWS network will play a critical role in any future national -network of networks‖ because those agencies are particularly interested in the atmospheric state in typically undersampled remote locations, as well as within increasingly important urban-wildland interface regions. Myrick and Horel (2008) evaluated the impact of RAWS observations on winter temperature and wind analyses in the western United States. That study demonstrated the the impact of removing RAWS observations on such analyses relative to the impact of removing Automated Surface Observing System (ASOS) and Automated Weather Observing System (AWOS) observations from primarily airport locations that are disseminated by the National Weather Service (NWS).…”
Section: Introductionmentioning
confidence: 99%
“…The RTMA process (De Pondeca et al 2011) includes an estimate of the analysis error-the method being specific to the analysis process. Myrick and Horel (2008) have studied the sensitivity of surface analyses to a particular type of observation.…”
Section: Introductionmentioning
confidence: 99%